REFLECTIONS ON REALITY: A REPRESENTATION ANALYSIS OF ETHICAL DILEMMAS IN BLACK MIRROR’S “CROCODILE” - Rinjani, Hayomi Gendis (Rubikon : Journal of Transnational American Studies, 2025)
This article explores the ethical complexities surrounding memory-extracting technologies by analyzing the speculative narrative of Black Mirror’s episode "Crocodile". Employing Stuart Hall’s representation theory as the main analytical framework and guided by Jawad’s research on brain-computer interface (BCI) ethics focusing on the ethical lenses of autonomy, privacy, and security, as well as responsibility and regulation, the study investigates how the Recaller device represents broader societal anxieties about surveillance, control, and the erosion of personal boundaries. Through content and discourse analysis, the research unpacks how “Crocodile” constructs meaning around the loss of individual agency and the moral consequences of technological overreach. The episode presents a dystopian world where memories are no longer private, forcing characters into ethically fraught situations. This study argues that the episode not only dramatizes the potential dangers of intrusive technologies but also reflects cultural fears about the future of privacy, autonomy, and moral responsibility. In doing so, it emphasizes the importance of critically assessing how emerging technologies might reshape societal values, ethics, and communication practices.